Solid-liquid extraction of bioactive compounds with antioxidant potential from Alternanthera sesillis (red) and identification of the polyphenols using UHPLC-QqQ-MS/MS - Mohd Hazli, Ummi Husni Aminah; Abdul-Aziz, Azlina; Junit, Sarni Mat; Chee, Chin Fei; Kong, Kin Weng (Elsevier, 2019)
Alternanthera sessilis (red) (ASR) is an edible herbal plant with many beneficial health effects. This study aimed to investigate the antioxidant components and antioxidant activities of the edible leaves and stems of ASR extracted using solvent of varying polarities namely water, ethanol, ethyl acetate and hexane. ASR leaf extracts showed higher in both antioxidant components and activities than the stem extracts. Among the antioxidant components, the ethanol leaf extract showed higher phenolic (77.29 ± 1.02 mg GAE/g extract) content while the ethyl acetate leaf extract was rich in flavonoids (157.44 ± 10.19 mg RE/g extract), carotenoids (782.97 ± 10.78 mg BE/g extract) and betalains (betanin: 67.08 ± 0.49 mg/g extract; amaranthin: 93.94 ± 0.68 mg/g extract and betaxanthin: 53.92 ± 0.88 mg/g extract). Nevertheless, the ethanol leaf extract showed the highest DPPH radical scavenging activity and ABTS radical cation scavenging activity. It also exhibited highest ferric reducing activity among all the extracts. Four polyphenolic compounds from ASR leaf, namely ferulic acid, rutin, quercetin and apigenin, were identified and quantified using ultra high performance liquid chromatography. The existence of these compounds was further verified using tandem mass spectrometry. These current results indicate that ASR leaf particularly the ethanol extract has the potential to be exploited as a source of natural antioxidants.